If G ( x ) = − 2 5 − x 2 , then evaluate x → 1 lim x − 1 G ( x ) − G ( 1 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
L = x → 1 lim x − 1 G ( x ) − G ( 1 ) = x → 1 lim x − 1 − 2 5 − x 2 + 2 5 − 1 = x → 1 lim 1 − 2 2 5 − x 2 − 2 x = 2 4 1 Given that G ( x ) = − 2 5 − x 2 A 0/0 cases, L’H o ˆ pital’s rule applies. Differentiate up and down w.r.t. x
Therefore, the answer is None of the others .
By the definition of derivatives
G ′ ( a ) = x → a lim x − a G ( x ) − G ( a )
obtaining the derivative G ′ ( x ) = 2 5 − x 2 x
Thus, x → 1 lim x − 1 G ( x ) − G ( 1 ) = G ′ ( 1 ) = 2 4 1
Problem Loading...
Note Loading...
Set Loading...
lim x → 1 x − 1 2 4 − 2 5 − x 2 = lim x → 1 x − 1 2 4 − 2 5 − x 2 ⋅ 2 4 + 2 5 − x 2 2 4 + 2 5 − x 2 = lim x → 1 x − 1 x 2 − 1 ⋅ 2 4 + 2 5 − x 2 1 = lim x → 1 2 4 + 2 5 − x 2 x + 1 = 2 4 1